A broadband quasi‐Yagi array of rectangular loops on LTCC. Issue 2 (2nd May 2013) - Wang, Jinhong; Sang, Lei; Wang, Zhigang; Xu, Ruimin; Yan, Bo
ABSTRACT In this article, a broadband quasi‐Yagi array of rectangular loops using low‐temperature co‐fired ceramic technology is proposed. The antenna is fed by a simple and compact microstrip‐to‐coplanar strip transition, which serves as balun and impedance transformer simultaneously. Four rectangular loops are used to direct the antenna propagation toward the end‐fire direction. Compared with the planar directors in traditional quasi‐Yagi antenna, they can provide better director effect to improve the radiation performance. Furthermore, they act as good impedance matching elements to broaden the bandwidth. The measured results show that the proposed antenna achieves a wide bandwidth of 42% for S11 < −10 dB (from 26.1 to 40 GHz), better than 12 dB front‐to‐back ratio, smaller than 14 dB cross polarization and an average gain over 6.5 dBi across the operating bandwidth. The antenna occupies a compact size of 8 × 8 × 1 mm3. © 2013 Wiley Periodicals, Inc. Int J RF and Microwave CAE 24:196–203, 2014.